Pharmacotherapy of Peptic Ulcer Disease - F Molina; MM Vohra; CN Williams (Canadian Journal of Gastroenterology)
The etiology of peptic ulcer is multifactorial; except for omeprazole, all drugs used for the treatment of peptic ulcer result in healing with no statistical difference at four weeks. The healing rare increases with time for active medication and placebo, and is lower among smokers than nonsmokers for all drugs but misoprostol. Mucosal protectives (or ‘cytoprotectives’) as a group seem to have a lower relapse rate than the H2 receptor antagonists at one year. Combination therapy has not yet proved to be better than single drug therapy; however, the number of studies is still small, and more clinical trials are necessary. Resistant ulcers have demonstrated that acid is one of several etiological factors and that more research is needed to elucidate the reason(s) for refractoriness. The choice of therapeutic agent is generally made according to patient compliance, medication cost, side effects, effectiveness, relapse rate and physician experience with the drug. Long term maintenance therapy is effective in the prevention of ulcer relapse and is especially recommended for selected patient groups, including patients with recurrent or bleeding ulcer, patients with concomitant nonsteroidal anti-inflammatory drug use, and elderly women. Omeprazole is the treatment of choice for moderate to severe esophagitis and should be reserved for large and resistant ulcers.